1988
DOI: 10.1159/000276000
|View full text |Cite
|
Sign up to set email alerts
|

Localization of IgE Synthesis in Immediate-Type Allergy of the Upper Respiratory Tract (With 3 color plates)

Abstract: The localization of allergen-specific IgE synthesis in allergic diseases of the upper respiratory tract is so far unknown. It has been suggested that the IgE production takes place in the nasal mucosa itself. The present immunohistochemical studies with anti-IgE and monoclonal markers for B lymphocytes, plasma cells, antigens of the major histocompatibility complex, T helper and T suppressor cells indicate that there are no IgE-producing plasma cells in the nasal mucosa of patients with seasonal allergic rhini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 21 publications
2
27
1
Order By: Relevance
“…Clinical studies have found a close association between asthma and serum IgE levels, and the amount of allergen-specific IgE can be dramatically increased in sensitized or atopy patients (7,8). Allergen-specific IgE is located in the human airway, such as in nasal mucosa from allergic patients who suffer allergic rhinitis in sinonasal tissue, nasal polyposis, and allergic fungal rhinosinusitis (9)(10)(11)(12). This observation is further supported by the fact that B cells from the nasal mucosa of allergic individuals locally synthesize IgE (13,14).…”
mentioning
confidence: 99%
“…Clinical studies have found a close association between asthma and serum IgE levels, and the amount of allergen-specific IgE can be dramatically increased in sensitized or atopy patients (7,8). Allergen-specific IgE is located in the human airway, such as in nasal mucosa from allergic patients who suffer allergic rhinitis in sinonasal tissue, nasal polyposis, and allergic fungal rhinosinusitis (9)(10)(11)(12). This observation is further supported by the fact that B cells from the nasal mucosa of allergic individuals locally synthesize IgE (13,14).…”
mentioning
confidence: 99%
“…The nasal mucosa itself contains all the cell types (dendritic cells, T-cells and B-cells [8] ) and cytokines (interleukin (IL)-4 and IL-13 [9±12]) necessary for an IgE immunoresponse. Other studies have suggested that IgE synthesis takes place in the downstream cervical lymph nodes [13,14] or upper respiratory and lower respiratory lymph nodes [15]. However no information has been obtained as to whether the IgE comes from the circulation (transudate) or from the mucosal glands (exudatate).…”
mentioning
confidence: 99%
“…Ganzer and Bachert (12) demonstrated that the production of IgE is not only limited to the nasal mucosa but also exists in the lymphatic tissue in Waldeyer's ring.…”
Section: Discussionmentioning
confidence: 99%